Intussusception in Five Months Old Infant, A Rare Cause Colocolica without Pathologic Lead Point: A Case Report - Yusri Dianne; Mutiara Annisa Amadea; Yorva Sayoeti (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2022)
Intussusception is a common cause in gastrointestinal obstruction and one of condition in which early treatment is critical. Given the risk of acute bowel ischemia, intussusception represents an abdominal emergency in the pediatric population. The symptoms are generally related to intestinal obstruction, as intussusception accounts for up to 50% of pediatric small bowel obstructions in some series. Colocolica intussusception is an uncommon type of intussusception in children that is usually associated with a pathological lead point. This report depicts a five-months-old female baby with a chief complaint of bloody stool 7 hours before admission, accompanied with non-bilious vomit. Patient exhibited the classic triad of intussusception and upon the radiologic examination, a colocolica was noted. Patient then underwent urgent exploratory laparotomy, and the colocolica was reduced through manual reduction (milking technique).